Advertisement call and male morphology of the Malagasy treefrog Boophis arcanus from the Ranomafana region, south-eastern Madagascar - Riemann, Jana C.; Ndriantsoa, Serge H.; Vences, Miguel; Rödel, Mark-Oliver; Glos, Julian (Zootaxa, 2012)
With over 70 nominal species, treefrogs of the genus Boophis (family Mantellidae) represent one of the most species-rich lineages in the amphibian fauna of Madagascar (Cadle 2003). Most Boophis are characterized by relatively loud and conspicuous calls, but specimens can be difficult to collect because males are often perched high on trees. Therefore, many species are so far only known from a few specimens, usually males. An exception is the recently described species Boophis arcanus, which is only known from two female specimens and for which no further biological data are available (Glaw et al. 2010). The two females were found at night sitting on trees and bushes in the rainforest of Mahakajy, a private reserve close to Ranomafana National Park (RNP) in the southern central east of Madagascar. Based on recordings and specimens collected during recent survey work in RNP and nearby forest fragments, we here describe male morphology and the advertisement call of this species.